A new species of the genus Psilota Meigen, 1822 (Diptera: Syrphidae) from China - Zhao, Le; Xin Liu; Smit, John T.; Li, Gang; Liu, Han-Yue; Dang, Li-Hong; Huo, Ke-Ke (Zootaxa, 2022)
The genus Psilota Meigen, 1822 is recorded for the first time from China, and the species Psilota bashanensis Huo and Zhao sp. nov. is described and illustrated based on the adult male. The complete cytochrome c oxidase subunit I (COI) gene of this new species has been successfully obtained and compared to that of other congeneric species. An updated key to adult males of the genus Psilota from the Palaearctic Region is also provided.